UJI PENGARUH TEPUNG AZOLLA (Anabaena azollae) DENGAN TAKARAN YANG BERBEDA PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA SRIKANDI (Oreochromis niloticus) - Sabbih Fatkhummubin; Rahmad Jumadi; Sa’idah Luthfiyah (Jurnal Perikanan Pantura (JPP), 2019)
This study was conducted to determine the effect of the provision of azolla flour into pellet feed to improve the performance of tilapia. This study used a complete randomized block (CRD) consisting of 4 treatments and 3 replications with doses, namely: (K - 100% pellet feed), (A - 75% + 25% Azolla pellet), (B – pellet 50% + 50 % Azolla), (C - pellet 25% + 75% Azolla) main parameters include weight growth, survival and feed conversion ratio (FCR), feed utilization efficiency (EPP). While supporting parameters include temperature, pH, DO. Then the data obtained was processed dst and analyzed using excel, analysis of variance (ANOVA) with a confidence of 95% and continued using BNT test. If there was a significant effect on the treatment. The ANOVA test results showed that the administration of azolla flour on feed did not have a significant effect on absolute growth and daily growth rate, survival FCR, and efficiency of feed utilization (EPP) of tilapia (p<0.05), thus the results of the study could be concluded the addition of azolla flour to tilapia feed in this study did not have a significant effect, so there was no need to do further tests on BNT0.05 (Smallest Significant Difference). The results in this study on absolute growth control treatment amounted to 0.83 gram, specific growth rate of 0.69%, FCR of 1.72, survival (SR) of 53% while feed utilization efficiency (EPP) of 43.82% no one has a real influence.